PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA EKONOMI PERUSAHAAN DENGAN KINERJA LINGKUNGAN SEBAGAI VARIABEL INTERVENING Studi Empiris pada Perusahaan yang Memperoleh Penilaian PROPER - Maulida Athiatul Ulya; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This research aims to examine the influence of corporate governance on the economic performance of companies and environmental performance as an intervening variable. Corporate governance are the proportion of independent Commissioners, institutional ownership, managerial and ownership. The economic performance of the company measured by ROA (Return on Assets) and environmental performance appraisal using PROPER published by the Ministry of Environment of the Republic of Indonesia. The sampling method was purposive sampling of 59 public listed companies awarded PROPER in 2010-2012. The data used path analysis by SPSS. The result indicated that the proportions of independent commissioner have a positive impact on environmental performance while the institutional ownership and managerial ownership have no affect on environmental performance. Supporting the previous study, environmental performance has a positive impact on economic performance. Environment performance capable of being variable intervening in connection between the proportion of independent commissioner, against ROA. But, environmental performance not capable of being variable intervening in connection between institutional ownership and managerial ownership, against ROA.